Sensor Array Geometry Acquisition by Spherical Coil Array for OPM-Based MEG System - Adachi, Yoshiaki; Oyama, Daisuke; Uehara, Gen; Zaatiti, Hadi (IEEE sensors journal, 2025)
Precise determination of sensor array geometry is critical for accurate magnetic source localization in magnetoencephalography (MEG). This is particularly important for optically pumped atomic magnetometer (OPM)-based MEG systems since their sensor array configuration can be flexibly modified depending on the subject's head shape. In this study, we demonstrate, for the first time, that a spherical coil array-previously validated for superconducting quantum interference device (SQUID)-based MEG-can also be applied to OPM-based MEG systems. Using a dry-type MEG phantom equipped with 49 equivalent current dipoles (ECDs), we evaluated the sensor array geometry obtained with the spherical coil array. We compared it with that derived from the method originally implemented in the OPM-MEG system. To isolate geometry-related effects, we incorporated two procedures: template fitting for field extraction and a recursive coordinate system transformation. These procedures minimized uncertainties not associated with the sensor array geometry in the ECD estimation. The results show that spherical coil calibration reduced the variability in the positional displacement between estimated and assumed ECDs in close (on-scalp) recordings by approximately 50%, as confirmed by 95% credible intervals. In the far mode, improvements were present but less pronounced. These findings indicate that the spherical coil array calibration enhances OPM-MEG source estimation by providing more accurate orientations and sensitivities. As a result, OPM-MEG measurements become more reliable, enabling broader applications in research and clinical settings.